Europec/Eage Conference and Exhibition 2008
DOI: 10.2118/113831-ms
|View full text |Cite
|
Sign up to set email alerts
|

The Benefits of Integrated Asset Modeling: Lesson Learned from Field Cases

Abstract: Nowadays oilfield development has become more technically and economically challenging and a high degree of interdisciplinary interaction is needed to have an effective and efficient management of the field. The achievement of this goal is made possible only if all the different resources of an organisation work together sharing the same reservoir model. Indeed, the main breakthrough behind Integrated Asset Modeling (IAM) is to combine reservoir, production and surface engineering modeling into an asset manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
8

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(17 citation statements)
references
References 46 publications
0
9
0
8
Order By: Relevance
“…In the assessment of some authors (Zapata et al, 2001;Rotondi et al, 2008), the explicit approach is quite flexible, however, the consistency between the network and the simulator computations should be checked because the IPR used by the simulator output is computed by solving the well equations with cells pressure and saturations at time t, while other variables, including well rates or pressures, are updated with the IPR holding at time t+∆t. This may induce discrepancy between reservoir bottom-hole and network bottom-hole when the wells are controlled by a controller program under a target fluid rate.…”
Section: Coupling Processmentioning
confidence: 99%
“…In the assessment of some authors (Zapata et al, 2001;Rotondi et al, 2008), the explicit approach is quite flexible, however, the consistency between the network and the simulator computations should be checked because the IPR used by the simulator output is computed by solving the well equations with cells pressure and saturations at time t, while other variables, including well rates or pressures, are updated with the IPR holding at time t+∆t. This may induce discrepancy between reservoir bottom-hole and network bottom-hole when the wells are controlled by a controller program under a target fluid rate.…”
Section: Coupling Processmentioning
confidence: 99%
“…Several recent methodologies [6][7][8] have tried to improve coupling reservoir models and production system models to simulate integrated solutions, representing fluid flow through the reservoir to the surface, more accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, more studies integrating reservoir and production systems in petroleum field production are needed to analyze the pressure interaction between reservoirs, wells, gathering networks, and surface facilities. Barroux et al (2000), Kosmala et al (2003), Rotondi et al (2008), and Cotrim et al (2011) demonstrated the necessity of integrated methodologies to couple simulators to improve production forecast reliability and quality. For instance, when the reservoir simulator fails to model the operational conditions of complex production systems, integration with the process simulator becomes even more consequential.…”
Section: Introductionmentioning
confidence: 99%